2020
DOI: 10.1093/ageing/afaa253
|View full text |Cite
|
Sign up to set email alerts
|

Early Mobilization in Older Adults with Acute Cardiovascular Disease

Abstract: Background Early mobilization (EM) is beneficial in critical care units and in older hospitalized patients, but little is known about EM in older adults with acute cardiovascular disease. Methods Consecutive admissions of adults ≥80 years old to a Cardiac Intensive Care Unit (CICU) prior to and following implementation of a nurse-driven EM program were reviewed. Mobility was measured using the Level of Function (LOF) Mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recently, the safety and efficacy of an early intervention in older patients with cardiovascular diseases, including HF, have been reported. A previous study of 412 older patients with cardiovascular disease (mean age, 86.3 years) revealed that early mobilization was safe and associated with reduced discharge to a healthcare facility and in‐hospital mortality among older patients admitted to the cardiac intensive care unit 29 . A previous study of 264 older patients admitted to the cardiovascular intensive care unit (mean age, 77.1 years) reported that early mobilization could be performed without patient falls, catheter or vascular line dislodgements, or healthcare personnel injuries 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the safety and efficacy of an early intervention in older patients with cardiovascular diseases, including HF, have been reported. A previous study of 412 older patients with cardiovascular disease (mean age, 86.3 years) revealed that early mobilization was safe and associated with reduced discharge to a healthcare facility and in‐hospital mortality among older patients admitted to the cardiac intensive care unit 29 . A previous study of 264 older patients admitted to the cardiovascular intensive care unit (mean age, 77.1 years) reported that early mobilization could be performed without patient falls, catheter or vascular line dislodgements, or healthcare personnel injuries 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of 412 older patients with cardiovascular disease (mean age, 86.3 years) revealed that early mobilization was safe and associated with reduced discharge to a healthcare facility and in-hospital mortality among older patients admitted to the cardiac intensive care unit. 29 A previous study of 264 older patients admitted to the cardiovascular intensive care unit (mean age, 77.1 years) reported that early mobilization could be performed without patient falls, F I G U R E 2 Acute-phase initiation of rehabilitation for the in-hospital mortality in each subgroup in the propensity score-matched cohort. Body mass index was classified into two groups by median (median value = 20 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“… 21 EM has also been shown to be safe, feasible, and effective in older adults with acute cardiovascular disease. 22 In addition to reducing in hospital sedentary time, EM may also improve mood and cognitive outcomes as well as reduce the functional decline associated with posthospitalization syndrome. 23 However, the bulk of the current evidence base for mobility programs is for mechanically ventilated patients in critical care units.…”
Section: Discussionmentioning
confidence: 99%